Gold-catalyzed 1,2-oxyalkynylation of N-Allenamides with ethylnylbenziodoxolones - Banerjee, Somsuvra; Senthilkumar, Beeran; Patil, Nitin T. (Organic Letters, 2019)
A gold-catalyzed 1,2-oxyalkynylation of N-allenamides with ethylnylbenziodoxolones (EBXs) has been achieved for the first time. The reaction, which follows a redox-neutral Au(I)/Au(III) catalytic pathway, was enabled in an attempt to exhaust the EBX reagents atom-economically by putting the nucleophilic carboxylate part of EBXs to appropriate use. This constitutes the first example for gold-catalyzed beta-alkynylation of N-allenamides to construct highly valuable 1,3-enynes. The potential of the sequence is further documented by some follow-up transformations.

Anthrone-spirolactam and quinoline hybrid based sensor for selective fluorescent detection of Fe(3+)ions - Darole, Ratanamala S.; Christopher Leslee, Denzil Britto; Mukherjee, Anagh; Gonnade, Rajesh G.; Karuppannan, Sekar; Senthilkumar, Beeran (2020)
The synthesis of a novel, and highly selective Fe(3+)ion sensor based on anthrone-spirolactam and its quinoline hybrid ligand is reported. The designed ligand displayed selective detection of Fe(3+)ions with enhanced fluorescence emission. The complexation of Fe(3+)ion led to a red shift of 32 nm from 420 nm to 452 nm, and a several fold increase in intensity with fluorescent green emission. The complexation (detection) of Fe(3+)ions with ligand resulted in chelation enhanced fluorescence and intramolecular charge transfer through the inhibition of C=N isomerization. This hybrid sensor shows high sensitivity and selectivity, spontaneous response, and works on a wide pH range a minimum detection limit of 6.83 x 10(-8)M. Importantly, the sensor works through the fluorescence turn-on mechanism that overcomes the paramagnetic effect of Fe(3+)ions. The binding mechanism between the ligand and the Fe(3+)ions was established from the Job's plot method, optical studies, Fourier transfor infrared spectroscopy, NMR titration, fluorescence life-time studies, and density functional theory optimization. The sensor displayed excellent results in the quantification of Fe(3+)ions from real water samples. Furthermore, due to its biocompatibility nature, fluorescent spotting of Fe(3+)ions in live cells revealed its bioimaging applications.
Keywords: anthrone-spirolactam-quinoline; Cell imaging; fluorescence; intramolecular charge transfer; iron

Gold-catalyzed alkynylative meyer-schuster rearrangement - Banerjee, Somsuvra; Ambegave, Shivhar B.; Mule, Ravindra D.; Senthilkumar, Beeran; Patil, Nitin T. (Organic Letters, 2020)
By applying the ``interplay'' mode, which consolidates two key reactivity modes of gold catalysis, namely pi-activation mode and cross-coupling mode, the first alkynylative Meyer-Schuster rearrangement is designed and successfully implemented. The current protocol gives straightforward access to enynones, a highly valuable building block, from easily available propargyl alcohol feedstocks. Control experiments suggest an Au(III) catalyst triggers the Meyer-Schuster rearrangement, whereas monitoring the reaction with ESI-HRMS provided strong evidence in favor of a key alkynylgold(III) intermediate which supports the proposed ``interplay'' scenario.

Influence of the ion size on the stability of the smectic phase of ionic liquid crystals - Cao, Wudi; Senthilkumar, Beeran; Causin, Valerio; Swamy, Vincent P.; Wang, Yanting; Saielli, Giacomo (Soft Matter, 2020)
The thermotropic phase behavior of ionic liquids and ionic liquid crystals based on novel N-alkyl-3-methylpyridinium halides, trihalides and dichloroiodates was experimentally studied by polarized optical spectroscopy (POM) and differential scanning calorimetry (DSC) as well as by molecular dynamics (MD) simulation. In the experiments, the existence and thermal range of stability of the smectic phase of these ionic liquid crystals are found to strongly depend on the volume ratio between the cation and anion, that is their relative size. Only compounds with a relatively large volume ratio of the cation to anion, i.e., those with longer cationic alkyl chains and monoatomic halide anions, have a stable smectic A phase. Both melting points and clearing points increase with such a ratio. The MD simulation results qualitatively agree very well with the experimental data and provide molecular details which can explain the experimentally observed phenomena: the stronger van der Waals interactions from the longer alkyl chains and the stronger electrostatic interactions from the smaller anions with a higher charge density increase the stability of both the crystal phase and the smectic phase; this also prevents the ionic layers from easily mixing with the hydrophobic regions, a mechanism that ultimately leads to a nanosegregated isotropic liquid phase.

Triethyl phosphite/benzoyl peroxide mediated reductive dealkylation of O-benzoylhydroxylamines: a cascade synthesis of secondary amides - Aegurla, Balakrishna; Mandle, Ram D.; Shinde, Prasad G.; Parit, Ratan S.; Kamble, Sanjay P.; Sudalai, Arumugam; Senthilkumar, Beeran (European Journal of Organic Chemistry, 2020)
A new triethyl phosphite/benzoyl peroxide (BPO) mediated system has been developed for the synthesis of secondary amides with good to excellent yields in a single step. This unprecedented cascade process involves sequential reduction of N-O bond and benzoylation followed by dealkylation of N-C bond ofO-benzoylhydroxylamines (O-BHA). The methodology is versatile as it tolerates a variety of aromatic and aliphaticO-BHA as substrates to access secondary amides.
Keywords: Amides; Cascade reactions; O-Benzoylhydroxylamines; Redox reactions; synthetic methods

Interplay of anion-pi(+) and pi(+)-pi(+) interactions in novel pyrido[2,1-a]isoquinolinium-based aiegens - substituent- and counterion-dependent fluorescence modulation and applications in live cell mitochondrial imaging - Mule, Ravindra D.; Roy, Rupam; Mandal, Koushik; Chopra, Deepak; Dutta, Tanoy; Sancheti, Shashank P.; Shinde, Popat S.; Banerjee, Somsuvra; Lal Koner, Apurba; Bhowal, Rohit; Senthilkumar, Beeran; Patil, Nitin T. (Chemistry-A European Journal, 2022)
Recently, the concept of anion-pi(+) interactions has witnessed unique applications in the field of AIEgen development. In this contribution, we disclose a consolidated study of a library of N-doped ionic AIEgens accessed through silver-mediated cyclization of pyridino-alkynes. A thorough photophysical, computational and crystallographic study has been conducted to rationalize the observed substituent- and counterion-dependent fluorescence properties of these luminogens. We further elucidate the prominent role of anion-pi(+) interactions, pi(+)-pi(+) interactions and other non-covalent interactions, in inhibiting the undesired ACQ effect. Finally, we have also demonstrated the application of selected AIEgens for imaging of mitochondria in live cells.
Keywords: 1-a]isoquinolinium; AIEgens; anion-pi(+); crystal structure; mitochondrial imaging; pyrido[2

Synthesis of novel rhodamine type anthrone Spiro-lactam (ASL) analogues and evaluation of antiviral activity against dengue and chikungunya viruses - Darole, Ratanamala S.; Bagad, Pooja K.; Gonnade, Rajesh G.; Alagarasu, Kalichamy; Punekar, Madhura; Shukla, Shridhar; Parashar, Deepti; Senthilkumar, Beeran (European Journal of Medicinal Chemistry, 2023)
A series of Rhodamine type Anthrone-Spirolactam (ASL) derivatives Benzylimin-Anthrone-Spirolactam (ASL-1 to ASL-10) and Benzamide-Anthrone-Spirolactam (ASL-11 and ASL-12) were synthesized via a simple condensation reaction between Anthrone Spiro-lactamine (2) and various aromatic aldehyde and acyl chlorides respectively. Since rhodamine-based compounds were reported to have antiviral activity, the ASL derivatives were examined for in vitro antiviral activity against dengue and chikungunya viruses. Among all the analogues, ASL-3, ASL-6, ASL-7, ASL-8, ASL-9 and ASL-10 were the most potent against dengue virus (DENV) and exerted around one log reduction in virus titre under post -treatment conditions. At the same time ASL-3 was effective under cotreatment conditions. Two analogues ASL-6 and ASL-12 exerted anti-chikungunya virus (CHIKV) activity under post -treatment conditions. In silico docking studies revealed that the ASL derivatives interacted with the proteins of DENV and CHIKV. Together, the results suggest the anti-DENV and CHIKV activity of ASL derivatives which may be exploited further for therapeutic purposes.
Keywords: Anthrone Spiro-lactam; Chikungunya virus; dengue virus; Rhodamine

Brønsted acid- and Ni(ii)-catalyzed C-H oxidation/rearrangement of cyclotriveratrylenes (CTVs) to cyclic and acyclic quinones as potential anti-cancer agents - Darole, Ratanamala S.; Choudhary, Shailendra Singh; Sharma, Himanshu; Mali, Bhupendra P.; Gopu, Booblan; Vanka, Kumar; Senthilkumar, Beeran (Organic and biomolecular chemistry, 2024)
This paper describes a simple and practical protocol for the direct synthesis of acyclic and cyclic quinone derivatives via an acid-promoted nickel(ii)-catalyzed inner rim C-H oxidation of cyclotriveratrylene (CTV) and its analogues. The cyclic quinone derivatives resulted from trimethoxy-cyclotriveratrylene (TCTV) through C-C bond formation via intramolecular ipso substitution followed by subsequent anionic rearrangement containing stereo-vicinal quaternary centers. The DFT calculations strongly support the experimental findings and reveal the role of Bronsted acids in the C-H bond activation of CTV. All the newly synthesized compounds were screened for their in vitro anti-cancer activity using colorimetric SRB assay analysis. Among them, compounds 3a, 3d, 3h, 4a, 4b, 4c and 4e exhibited moderate anticancer activity against A549, HCT-116, PC-3, MDA-MB-231, HEK-293 and SW620 human cancer cell lines.

Highly selective C-N and C-S dual functionalization of 1,3-dicarbonyl derivatives using TBHP as an oxidant - Bagad, Pooja K.; Darole, Ratanamala S.; Krishna, G. Rama; Senthilkumar, Beeran (Journal of Organic Chemistry, 2024)
A direct electrosynthesis/photocatalyst-free, atom-economical, and efficient method for the selective synthesis of (E)-3-amino-2-thiocyanato-alpha,beta-unsaturated carbonyl compounds is described through a given protocol. The present approach features the use of inexpensive ammonium thiocyanate to achieve dual functionalization of 1,3-dicarbonyl compounds using TBHP as an oxidant, providing a rapid and practical route to the selective formation of both C-N and C-S bonds via a radical process. This method offers a broad substrate scope with excellent yield and allows for further exploration of the products to construct heterocyclic compounds and other functionalities.

Accessing polysubstituted 2-cyclopentenones via base-mediated annulation of β-keto esters and phenacyl bromides - Kumar, Mohit; Paul, Vincent; Gamidi, Rama Krishna; Senthilkumar, Beeran (Organic & Biomolecular Chemistry, 2025)
A transition metal-free method is demonstrated for the synthesis of polysubstituted 2-cyclopentenone compounds, which involves the direct annulation of phenacyl bromide with beta-keto esters in a single step. This process proceeds through a base-mediated SN2 nucleophilic substitution, followed by an intramolecular aldol condensation, resulting in the formation of three C-C bonds and one ring in a cascade manner. The experimental results achieved a record high yield of highly substituted diverse 2-cyclopentenone analogues, which exhibit very good structural resemblance to biologically significant natural compounds.

Base mediated approach for the synthesis of deoxybenzoins using γ-aryl-β-ketoesters and benzoyl chlorides - Choudhary, Shailendra Singh; Darole, Ratanamala S.; Krishna, Gamidi Rama; Senthilkumar, Beeran (RSC Advances, 2025)
This study introduces a one-pot, transition metal-free strategy for synthesizing deoxybenzoins, overcoming the challenges of conventional methods. The reaction involves dual acylation of gamma-aryl beta-keto esters using K2CO3 in dioxane at 90 degrees C, followed by a concerted transformation to form deoxybenzoin. The protocol operates under mild conditions, tolerates a broad range of substrates, and produces minimal by-products, making it a practical, scalable alternative for accessing pharmaceutically relevant deoxybenzoins.

Effectiveness of 3-amino-2-thiocyanato-α, β-unsaturated carbonyl compounds against chikungunya virus - Alagarasu, Kalichamy; Dhote, Radhika; Bagad, Pooja K.; Kharikar, Dwidhesh; Patil, Poonam; Roy, Diya; Shukla, Shridhar; Cherian, Sarah; Senthilkumar, Beeran; Parashar, Deepti (Future Medicinal Chemistry, 2025)
Aim Chikungunya fever (CHIKF) caused by the chikungunya virus (CHIKV) is characterized by the presence of long-term polyarthralgia in a minor proportion of the infected patients. Currently, there are no FDA-approved antivirals available. This study evaluated the anti-CHIKV potential of 16 synthetic 3-amino-2-thiocyanato-alpha, beta-unsaturated carbonyl compounds and elucidated their probable mechanisms of action. Methods Anti-CHIKV activity of 16 compounds were investigated in Vero CCL-81 cells using focus forming unit assay (FFU). Dose-dependent and time-dependent antiviral assays were performed for the effective compounds. Molecular docking was performed to find out their interactions with viral proteins. Results Five compounds showed promising anti-CHIKV activity by reducing viral titer with >1 log10 FFU/ml. Dose-dependent studies revealed that the compound 3 g was more effective in reducing the virus titer with a half-maximal inhibitory concentration (IC50) of 0.4315 mu M and a selectivity index of 35.99. Docking analyses revealed that all the compounds mainly interact with the non-structural proteins of CHIKV. Conclusions These findings demonstrate the in vitro anti-CHIKV activity of these compounds, and their possible mode of action via interference with early stages of infection and replication processes. This study warrants further preclinical and clinical evaluation to establish their safety and efficacy as novel anti-CHIKV therapeutics.
Keywords: 3-amino-2-thiocyanato-alpha; antivirals; beta-unsaturated carbonyl compounds; Chikungunya virus (CHIKV); nsP2 helicase; therapeutics

Synthesis, crystal structure, DFT calculation and catalytic activity of a polymer complex of zinc(II) succinate with 2-amino-1,3,4-thiadiazole - Nuralieva, Guzal; Alieva, Mushtariy; Torambetov, Batirbay; Leslee, Denzil Britto Christopher; Senthilkumar, Beeran; Kaur, Simranjeet; Dabke, Niteen B.; Vanka, Kumar; Ashurov, Jamshid; Kadirova, Shakhnoza; Gonnade, Rajesh G. (Journal of Molecular Structure, 2025)
A polymer complex of zinc(II) succinate with a 2-amino-1,3,4-thiadialole ligand, denoted as [Zn2L2(suc)2]n, was synthesized and characterized by NMR, ESI-MS, FTIR, and FT-Raman spectroscopy, TGA, and X-ray crystallography. The polymer complex crystallizes in the orthorhombic noncentrosymmetric Pna21 space group and features a five-coordinate zinc ion in a distorted spherical square pyramidal geometry. The Hirshfeld surface analysis was carried out to evaluate the intermolecular interactions. Additionally, computational studies were also conducted to assess the stability of the Zn polymer complex and analyze the electron density distribution of the HOMO and LUMO. The catalytic activity of our complex was tested, interestingly, that showed good results for Biginelli reactions with distinct substrate scope in good to high yield at mild reaction conditions.
Keywords: DFT; Dihydropyrimidinones; Polymer complex; succinate; Thiadiazole; zinc